1990
DOI: 10.1080/0260747900160203
|View full text |Cite
|
Sign up to set email alerts
|

Research on Teachers’ Thinking: its contribution to educating student teachers to think critically

Abstract: A substantial body of published research has investigated teacher thinking and it claims to be relevant for teacher-educators who wish to foster student teachers' critical reflection. Basic issues concerning this research are examined critically, with particular reference to its value for teacher-educators. In the light of this assessment, proposals are made as to how teacher-educators may ensure that student teachers become reflective practitioners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
3

Year Published

1993
1993
2012
2012

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(32 citation statements)
references
References 23 publications
(17 reference statements)
1
28
0
3
Order By: Relevance
“…The terms of reflection, critical reflection, reflective practice and reflective inquiry have all been used interchangeably to describe the same concept. Nevertheless, there is a general agreement in the literature that reflection in teacher education is a special form of thought (McNamara, 1990;Sparks-Langer & Colton, 1991). Dewey (1933) reasoned that reflection precedes intelligent action.…”
Section: Reflective Practice In Teacher Educationmentioning
confidence: 98%
See 1 more Smart Citation
“…The terms of reflection, critical reflection, reflective practice and reflective inquiry have all been used interchangeably to describe the same concept. Nevertheless, there is a general agreement in the literature that reflection in teacher education is a special form of thought (McNamara, 1990;Sparks-Langer & Colton, 1991). Dewey (1933) reasoned that reflection precedes intelligent action.…”
Section: Reflective Practice In Teacher Educationmentioning
confidence: 98%
“…This finding is in keeping with the literature on reflection that says it is a special form of thought. (McNamara, 1990;SparksLanger & Colton, 1991). The definitions given by the five pre-service teachers fit with the literature on reflection on action, where Schon (1983) suggested that teachers think back on what they had done in order to determine what improvements could be made in the future.…”
Section: Acquiring Perspectivesmentioning
confidence: 99%
“…(p. 151) Arguments for the dominant role of the university in initial teacher preparation have focused on a number of claims related to the unique characteristics of the university and to the nature of teaching. Perhaps foremost has been the university's value in promoting access to theory and research thus supporting teachers in developing a reflective and critical stance in relation to practice (Furlong et al 1996;McNamara, 1990McNamara, , 1996. Underpinning such arguments is the notion of teaching as an intellectual and moral activity before it is a technical one, and a model of teacher development which involves a sharing and distillation of practice, with a critical reflection on such practice in the light of research evidence and other theoretical perspectives in order to develop individual professional autonomy and responsibility (Hoyle & John, 1995).…”
Section: Discussionmentioning
confidence: 98%
“…These prescriptions ran ge from pedagogical 10 e thi cal a nd mo ral iss ues (Adler. 199 1: Gore, 1990: McN amara. 1990: Zeic hn er & Tabachnick.…”
Section: Dill/ellsiolls Oimicrorejlecliollmentioning
confidence: 99%